Chelate Bonding Mechanism in a Novel Magnesium Phosphate Bone Cement. Issue 3 (31st January 2015) - Christel, Theresa; Christ, Susanne; Barralet, Jake E.; Groll, Jürgen; Gbureck, Uwe
Abstract : A novel approach to harden magnesium phosphate cements was tested using phytic acid (C6 H18 O24 P6 ) solutions as chelation agent. In addition to complex formation, a cementitious dissolution and precipitation reaction led to the formation of newberyite (MgHPO4 ·3H2 O) as the hydrated form of the farringtonite [Mg3 (PO4 )2 ] raw powder. The set cements showed good mechanical properties (up to 65 MPa in compression) displaying a doubling of the compressive strength of conventional newberyite forming cements despite of a significantly lower degree of cement conversion. An increasing phytic acid concentration from 10% to 30% had a retarding effect on the setting time (11–16 min), decreased the pH close to acidic conditions (pH = 5–4) and increased the maximum setting temperature (26°C–31°C), but none of these factors reached critical values. The presented strategy was successful in fabricating a good workable, novel mineral biocement with promising characteristics for biomedical applications.